Testing the validity of purchasing power parity between ASEAN-4 and Singapore and its connections with CEPT scheme / Abdul Rahim Ridzuan, Elsadig Musa Ahmed and Lee Chin - Ridzuan, Abdul Rahim; Musa Ahmed, Elsadig; Lee, Chin (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Association of South East Asian Nations (ASEAN) countries has already started to fully implement the agreement on Common Effective Preferential Tariff (CEPT) scheme among its member’s countries on 1st January 2010. The progress on achieving this aim has taken many years and it is interesting to capture the significance of CEPT scheme towards realizing the equal Purchasing Power Parity (PPP) for the selected members of ASEAN countries so far. This paper applies the cointegration test to investigate the evidence of PPP in two different sample periods, which is before and after the implementations of CEPT Scheme between ASEAN-4 and Singapore. This study detects strong presence of PPP between Malaysia and Singapore after the implementation of CEPT. It shows that the goods market between these two countries is really integrated and thus the law of one price is fill filling here.